2013
DOI: 10.2478/afmnai-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence in Outpatients with Arterial Hypertension

Abstract: The degree of patient cooperation plays a key role in the success of antihypertensive drug therapy. Non-adherence is the major health and economic problem in the treatment of arterial hypertension (HTA). The aim of the study was to evaluate the degree of adherence in hypertensive patients and to study risk factors affecting adherence and the effects of non-adherence on blood pressure (BP). We performed a cross-sectional study, which involved 170 outpatients with HTA, treated in primary healthcare. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 16 publications
2
15
0
2
Order By: Relevance
“…On the other hand, a significantly lower level of adherence was identified in a study with elderly patients in Serbia. In this study patients less than 65 years were found to be more likely to adhere to their prescribed treatment, compared to older patients (AOR = 6.0; 95% CI: 2.76 -13.04) [28].…”
Section: Demographic Factorsmentioning
confidence: 86%
See 3 more Smart Citations
“…On the other hand, a significantly lower level of adherence was identified in a study with elderly patients in Serbia. In this study patients less than 65 years were found to be more likely to adhere to their prescribed treatment, compared to older patients (AOR = 6.0; 95% CI: 2.76 -13.04) [28].…”
Section: Demographic Factorsmentioning
confidence: 86%
“…Hypertensive patients who experienced side effects of their medications were less adherent to their medication than those who did not experience side effects in Palestine (AOR = 4.58; 95% CI: 1.87 -11.25) and Serbia (OR = 7.95; 95% CI: 1.48 -42.6) [28] [38]. Qualitative studies in Malaysia [51] and Nigeria [40] also found perceived side effects were inhibitors of antihypertensive medication adherence.…”
Section: Mmas 4 Ethiopia; N = 384 Open Journal Of Epidemiologymentioning
confidence: 90%
See 2 more Smart Citations
“…About 80% of this burden occurred in low-and middle-income countries 5,6 . The levels of awareness, treatment and control of hypertension vary between countries and are particularly low in some economically developing countries.…”
mentioning
confidence: 99%